Lectotypification, epitypification and taxonomic notes on Oenothera fallax (Onagraceae) - Woźniak-Chodacka, Monika (Phytotaxa, 2023)
In the protologue of Oenothera fallax Renner did not indicate any herbarium specimen to serve as a type. Instead, the author provided a brief German description and some black and white illustrations, presenting only the chosen features of the species. The collection of Renner stored in Herbarium in München (M) does not include the type of Oenothera fallax. Thus, the photos given by Renner are the only elements of original material from which a lectotype was selected. Because the lectotype does not include all the characteristics essential for the proper identification of the taxon, a specimen from Krzysztof Rostański collection stored in herbarium WRSL is selected to serve as an epitype supporting the lectotype. A short description of Oenothera fallax as well as a summary of taxonomy of the genus Oenothera are also provided.